2007
DOI: 10.1093/rheumatology/kem136
|View full text |Cite
|
Sign up to set email alerts
|

LPS-evoked IL-18 expression in mesangial cells plays a role in accelerating lupus nephritis

Abstract: We conclude that LPS can evoke IL-18 production in MCs, but neither LPS nor IL-18 directly induces apoptosis or activates apoptotic signal transduction in the cells. We infer that LPS-induced IL-18 production by MCs could be a mediator by which LPS accelerates and exacerbates LN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
52
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 34 publications
4
52
0
Order By: Relevance
“…10 Although this model is similar to the anti-Thy1 nephritis model in rats, the degree of mesangiolysis is not as profound (data not shown; see Yo et al 10 ) and requires additional application of LPS to aggravate mesangial injury. 11,12 In several pilot experiments combining anti-mesangial cell serum with varying doses of either Habu snake venom (data not shown) or LPS, we determined the best model system with maximal mesangial cell injury without an increase in mortality, which was used for all further experiments. On days 2-3, the optimized LPS/anti-mesangial cell serum-induced experimental disease model revealed overall pronounced mesangiolysis at varying degrees in individual glomeruli, which was followed by cellular repopulation up to days 10-13 ( Figure 1) as indicated by several lines of evidence.…”
mentioning
confidence: 99%
“…10 Although this model is similar to the anti-Thy1 nephritis model in rats, the degree of mesangiolysis is not as profound (data not shown; see Yo et al 10 ) and requires additional application of LPS to aggravate mesangial injury. 11,12 In several pilot experiments combining anti-mesangial cell serum with varying doses of either Habu snake venom (data not shown) or LPS, we determined the best model system with maximal mesangial cell injury without an increase in mortality, which was used for all further experiments. On days 2-3, the optimized LPS/anti-mesangial cell serum-induced experimental disease model revealed overall pronounced mesangiolysis at varying degrees in individual glomeruli, which was followed by cellular repopulation up to days 10-13 ( Figure 1) as indicated by several lines of evidence.…”
mentioning
confidence: 99%
“…[25][26][27][28][29][30] Macrophage accumulation in association with increased IL-18 expression has been described in a number of inflammatory and immune-mediated processes. 29,31 We previously described IL-18 upregulation within the kidney during acute rejection in a kidney allograft model and found intragraft macrophages to be the major source.…”
mentioning
confidence: 99%
“…Their further in vitro studies suggested that up regulation of renal IL-18 is a prerequisite for the local inflammatory cytokine cascade especially that the interaction between TNF and IL-18 might provide a positive-amplification loop that accelerates the auto-immune kidney disease. In addition to a possible role of IL-18 in the induction of apoptosis in tubular epithelial cells, 13 Shui et al 40 also demonstrated IL-18 overexpression, associated with hyperplasia and apoptosis of mesangial cells in the glomeruli of lipopolysaccharid-accelerated LN mice. They suggested that local IL-18 in the nephritic kidneys could act like a paracrine cytokine to exacerbate glomerular inflammation and is probably involved in the apoptosis of the downstream tubular cells.…”
Section: Discussionmentioning
confidence: 99%